Curcumae Rhizoma: A botanical drug against infectious diseases - Wu, Ying-Qi; Tong, Tong (Frontiers in Pharmacology, 2023)
Curcumae Rhizoma is the dry rhizome derived from Zingiberaceae species that grow widely in tropical south and southwest Asia. It has been used to treat conditions such as dermatoses, infections, stress, and depression. Moreover, in China, Curcumae Rhizoma and its active constituents have been made into different pharmaceutical preparations. Growing evidence suggests that these preparations can exert antioxidant, anti-inflammatory, and anti-cancer effects, which may play crucial roles in the treatment of various diseases, including cancer, infectious-, autoimmune-, neurological-, and cardiovascular diseases, as well as diabetes. The anti-infective effect of Curcumae Rhizoma has become a popular field of research around the world, including for the treatment of COVID‑19, influenza virus, hepatitis B virus, human immunodeficiency virus, and human papilloma virus, among others. In this paper, the basic characteristics of Curcumae Rhizoma and its active constituents are briefly introduced, and we also give an overview on their applications and mechanisms in infectious diseases.